Analisis Pengelolaan Keuangan Zakat Pada BAZNAS Berdasarkan Peraturan BAZNAS Nomor 5 Tahun 2018 - Fachrurazi; Pratiwi Kurniati; Nia Apri Soqdiah (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2022)
This study aims to find out whether budgeting, receiving funds, depositing funds, disbursing funds, bookkeeping, filing and controlling zakat funds at BAZNAS Melawi Regency have adjusted BAZNAS regulations Number 5 of 2018 concerning Zakat Financial Management. This study used a qualitative descriptive research method which was measured using observation data, interviews and documentation. This research was conducted at the National Amil Zakat Agency (BAZNAS) in Melawi Regency. The results of this study indicate that: 1) Zakat budgeting in BAZNAS, Melawi Regency, the preparation of the budget has not been prepared in the form of an Annual Work Plan and Budget (RKAT). 2) Each receipt of zakat funds in the form of money either through the zakat funds reception counter or electronically must issue proof of deposit. Regarding the distribution of zakat funds, the management explained the purpose for which these funds were allocated, of course these funds were inseparable from the 8 asnaf who were entitled to receive zakat. 3) Zakat funds must be stored in a place that has an adequate security system with a clear person in charge. 4) The issuance of zakat funds at BAZNAS of Melawi Regency has not been included in the Annual Work Plan and Budget (RKAT), must obtain approval from the authorized official. 5) Bookkeeping BAZNAS for Melawi Regency records and is recognized according to the amount distributed to mustahik. BAZNAS of Melawi Regency still manages manual and conventional bookkeeping, 6) Archiving, for proof of the release of the filing budget at BAZNAS of Melawi Regency there are 3 banks 2 sharia 1 including a conventional bank. 7) The existence of a control system can provide adequate guarantees for the achievement of efficiency and effectiveness of zakat management. So that the purpose of the zakat can be achieved.